2017
DOI: 10.1186/s12882-017-0634-2
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and outcomes of haemodialysis among patients presenting with kidney diseases in Dodoma, Tanzania

Abstract: BackgroundKidney Diseases contribute a significant proportion to the global burden of non-communicable diseases. Haemodialysis services as the main modality of renal replacement therapy in most resource limited countries is only available in few cities and at higher costs. The aim of this study was to determine the challenges and outcomes of patients who were on haemodialysis at the University of Dodoma (UDOM) haemodialysis unit in Tanzania.MethodsIn this retrospective study; we reviewed haemodialysis register… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 24 publications
3
30
1
Order By: Relevance
“…A high percentage (43.6%) of patients were lost to follow up during this period due to reasons which may not be unrelated to inancial constraints, traditional belief, and concept about the disease among others. A similar igure was reported by Meremo et al in Tanzania [16] and Bello et al in a Nigerian study [8]. Causes of death were inadequate dialysis due to inancial constraints with its attendant complications, poor compliance to medication including antihypertensive, and sepsis among others.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A high percentage (43.6%) of patients were lost to follow up during this period due to reasons which may not be unrelated to inancial constraints, traditional belief, and concept about the disease among others. A similar igure was reported by Meremo et al in Tanzania [16] and Bello et al in a Nigerian study [8]. Causes of death were inadequate dialysis due to inancial constraints with its attendant complications, poor compliance to medication including antihypertensive, and sepsis among others.…”
Section: Discussionsupporting
confidence: 80%
“…This grossly fell short of the recommended target as outlined by Kidney Disease Outcomes Quality Initiative (KDOQI) [15]. Similarly, an unacceptable low number of patients having inadequate frequency of dialysis was documented by other researchers [5,8,16]. Almost all our patients paid out of pocket without any inancial aids from the government hence they could not cope with the cost implication of dialysis.…”
Section: Discussionmentioning
confidence: 73%
“…Meremo et al published the challenges and outcomes of HD center in Dodoma, Tanzania, where we supported to establish HD center at 2013 [16]. They have had no experiences to treat HD at the beginning of 2013, but they treated 116 patients with HD from January 2013 to June 2015.…”
Section: Summary On Hd Supportmentioning
confidence: 96%
“…Meremo et al demonstrated that renal transplantation is not performed in Tanzania and only a few patients can afford going abroad [16], especially to India until 2017. Kidney transplant recipient, donor, and a person who takes care of them go to India and stay there for a few weeks for the kidney transplant operation, after that they come back to Tanzania and get immunosuppressants from the hospital in Tanzania.…”
mentioning
confidence: 99%
“…Haemodialysis services in Tanzania are largely reimbursed by the National Health Insurance Fund (NHIF), others pay 'out of pocket' and for a few patients HD services are covered by other private insurance or companies. Those paying 'out of pocket' may not be able to afford HD services and have higher risk of poor outcomes after initiation of HD [4]. This can be attributed to non-adherence to the standard three times per week HD.…”
Section: Prevalence Of Malnutrition In Ammation Complex Syndrome Amonmentioning
confidence: 99%